Thermodynamic and resonant properties of mixed spin compounds ACuFe2(VO4)3 (A = Li, Na) - Koshelev, Anatolii; Shvanskaya, L.; Volkova, O.; Zakharov, K.; Theuss, Florian; Koo, Changhyun; Klingeler, Rüdiger; Kamusella, S.; Klauss, H. -H.; Kundu, S.; Bachhar, S.; Mahajan, A. V.; et al. (Journal of alloys and compounds, 2020)
We report a combined experimental and theoretical study on magnetism and magneto-electric coupling in howardevansite-type mixed-spin chain compounds ACuFe2(VO4)3 (A = Li, Na). While LiCuFe2(VO4)3 shows long-range magnetic order and spin-order-induced ferroelectricity, i.e., multiferroicity of type II, neither magnetic order nor magneto-electric effects are observed in the Na-based sister compound. Notably, our local magnetic probes studies by means of NMR, ESR, and Mössbauer spectroscopy evidence similar magnetic behavior of both compounds at the time scales of these experiments. This is confirmed by first principles calculations which imply a similar hierarchy of exchange interaction parameters. Our results suggest that the absence of magneto-electric effects in NaCuFe2(VO4)3 as seen in bulk measurements is a disorder effect associated with lower mobility of Na ions within the channels of the crystal structure as compared to the mobility of Li ions, thereby presenting a yet disregarded degree of freedom to tune the multiferroicity.